The regional variation of new technology based firms in Austria - Josef Frohlich; Helmut Gassler (European Regional Science Association (ERSA), 1998)
During the last two decades the role of new business start-ups has gained a growing interest both from regional economics as well as from (regional) economic policy. It was recognized that not only the large Galbraithian enterprise is the driving force in processes like employment growth or structural economic change, but also small and often new or young firms are playing an active role. In the 1980s so called new technology based firms (NTBFs) gained considerable attention. It has been argued that the Schumpeterian entrepreneur is an important force for the implementation of new ideas into the market place, often via the formation of NTBFs. In our paper we analyse the structure and the regional variation of new business formation in the high technology sector in Austria. Using a definition based upon the OECD we differentiate the high tech sector in (i) top technology, (ii) higher technologies and (iii) technology orientated services. We demonstrate the relative importance of these groups for the total population of new business start-ups in Austria in the time period ot 1990-1994 as well as for certain sub-populations like manufacturing and services. The main part of our paper discusses the regional variation of NTBFs using the framework of the well known urban incubator hypothesis. It is expected that metropolitan and urban regions have a higher orientation towards high tech (what means the proportion of NTBFs) than the rural or hinterland regions. An additional part of our paper deals with the question wether NTBFs play an important role in the process of structural change of regional economies as has been postulated by various authors during the last couple of years.
Keywords: 330